A review of some of experimental and numerical studies of self‐crack‐healing in ceramics. Issue 6 (26th October 2020) - Hammood, Israa; Barber, Gary; Wang, Bingxu
Abstract: Ceramics can be used in many applications including aeroengine turbine blades, gas turbine blades, high‐performance bearings, and many other applications that require high temperature service; however, these ceramics are subjected to thermal and mechanical stresses during/while being used in service. Residual stresses may eventually cause microcracks (internal and surface cracks) and the failure of the component in use, hence limiting their use as structural engineering materials; for this reason, applying or inducing self‐crack‐healing ability would be the solution to overcome such problems. Developing new materials with an inherent ability to heal the cracks and increasing resistance to fracture wear and corrosion has been the goal for many researchers in the field of science and engineering and manufacturers. Great benefits can be expected from the components in use while applying self‐healing ability, such as reducing maintenance, inspection, and the cost of machining and polishing, which enhance the reliability and the lifespan of the component in use hence meeting the needs of many industries like automotive, space, aerospace. Consequently, many attempts have been made to imitate the mechanisms of biological systems to design self‐healing materials and coatings which can result in complete recovery and functionality of the component. These research studies are reviewed and summarized in this review manuscript. Abstract : A review on the self‐healing behavior, concept and processes, was done in this paper covering the research that has focused on the experiments and modeling of this behavior in ceramics and its composites.The research studies on self‐crack‐healing are reviewed and summarized in this review manuscript.